TRANSFORMASI STRUKTURAL: FAKTOR-FAKTOR DAN PENGARUHNYA TERHADAP DISPARITAS PENDAPATAN DI MADURA - Mohammad Saedy Romli; Manuntun Parulian Hutagaol; Dominicus Savio Priyarsono (IPB University, 2016)
Structural transformation is responsible for income disparity as transformation of economical structure is not supported by structural transformation of labor. This unbalanced transformation divides labour into two groups, unskilled and skilled labour. Increased income disparity is a consequence of different opportunity and intensive. This study investigated factors that account for structural transformation and its impact on disparity of income distribution in Madura using regression model of panel data. The results showed that population and income per capita significantly influenced structural transformation in Madura. Both factors significantly changed added value in agriculture and industry sector, meanwhile population was a single factor that significantly influenced service sector. Agriculture was a share sector that was effective in lowering income disparity. However, share sector of industry and service was observed to increase income disparity.